2012
DOI: 10.1111/j.1749-4486.2012.02455.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of relapses of nasal polyposis with intranasal triamcinolone acetonide after polyp surgery: A prospective double‐blind, placebo‐controlled, randomised study with a 9‐month follow‐up

Abstract: Triamcinolone acetonide prevents regrowth of nasal polyps after polyp surgery in acetylsalicylic acid-tolerant patients, but not in acetylsalicylic acid-intolerant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…r Triamcinolone was studied in 1 trial. 1003 Outcomes included individual and overall symptoms scores, endoscopic/polyp scores, QoL questionnaires, objective assessments of olfaction and airway and occasionally asthma score, number and time to relapse, or prevention of reoperation. A summary of outcomes is provided in Table VIII-7, with the majority demonstrating a significant benefit from the use of INCS as sprays or drops.…”
Section: Viiie Crswnp: Managementmentioning
confidence: 99%
“…r Triamcinolone was studied in 1 trial. 1003 Outcomes included individual and overall symptoms scores, endoscopic/polyp scores, QoL questionnaires, objective assessments of olfaction and airway and occasionally asthma score, number and time to relapse, or prevention of reoperation. A summary of outcomes is provided in Table VIII-7, with the majority demonstrating a significant benefit from the use of INCS as sprays or drops.…”
Section: Viiie Crswnp: Managementmentioning
confidence: 99%
“…24 One cohort study (n ϭ 32) 18 reported normal ACTH levels measured before and 1 hour after removal of corticosteroid-soaked packing gauze. 18 The reported adverse events from the included studies were blood-stained mucus, [22][23][24][25] mild epistaxis, 15,17,19 and nasal dryness. 22,23,26 …”
Section: Standard-dose Versus High-dose Incsmentioning
confidence: 99%
“…SD was calculated from the p value and given means estimated from the graph. 23, 25 Vento 23 reported that triamcinolone in comparison with placebo appeared to prevent polyp regrowth in acetysalicylic acid (ASA)-tolerant patients (p ϭ 0.03) measured at 9 months but not in ASAintolerant patients (p ϭ 0.28). The corresponding author was contacted and he provided the SD for each group.…”
Section: Endoscopic Score-polyp Sizementioning
confidence: 99%
See 1 more Smart Citation
“…8 In another study, we found a clear difference between the ASA-tolerant and ASA hypersensitivity groups, with the effect of triamcinolone acetonide being significant among the ASA-tolerant group. 9 It has been speculated that montelukast does not directly cause Churg-Strauss. All Churg-Strauss patients receiving LTRA have been treated for moderate/severe asthma with corticosteroid, but actually, they have had unmasked underlying vasculitic syndrome.…”
Section: Discussionmentioning
confidence: 99%